Matter generates the idea: experiments in the architectural education - Fausto Novi; Andrea Giachetta; Chiara Piccardo (Agathón)
The educational experiments mentioned below are aimed at demonstrating how matter, technique and technology can play their role in the architectural design as main elements of inspiration and development. These elements do not constitute a feared limitation to the designer’s creative freedom, also favoring the integration of scientific and technical training (at least for what learned in the early years) with design idea. The focus on materials as possible generators of ideas seems to be a good method to acquire the awareness of the responsibility for design action, since this is a problem-solving activity and not a free, ‘creative’ and uncontrolled activity.